2022
DOI: 10.21608/jcese.2022.266566
|View full text |Cite
|
Sign up to set email alerts
|

X-Gamma Lomax Distribution with Different Applications

Abstract: The X-Gamma Lomax (XGLo) distribution, a new three-parameter modification of the Lomax distribution, was introduced and examined in this study. This distribution's features for reliability and hazard rate are addressed. The methods for estimating the XGLo distribution parameters using maximum likelihood estimation (MLE) and maximum product spacing (MPS) are explained. To compare the MLE and MPS estimate approaches, a numerical investigation is conducted Monte-Carlo simulation. Three real data sets as the cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The GPA distribution is used in this section to model several real data examples from many scientific domains. Different distributions, including Weilbull, Lomax, XGamma Lomax (XGL) Almetwally et al [30], Inverse Weibul (IW), Inverted Nadarajah-Haghighi (INH), Tahir et al [31], and Akshaya distribution, are offered for comparison with the GPA distribution.…”
Section: Applicationmentioning
confidence: 99%
“…The GPA distribution is used in this section to model several real data examples from many scientific domains. Different distributions, including Weilbull, Lomax, XGamma Lomax (XGL) Almetwally et al [30], Inverse Weibul (IW), Inverted Nadarajah-Haghighi (INH), Tahir et al [31], and Akshaya distribution, are offered for comparison with the GPA distribution.…”
Section: Applicationmentioning
confidence: 99%
“…For more information about simulation study see [10], [11], and [12]. Hence, we assess the performance of the MLE using correct initial values and an obvious algorithm as follows:…”
Section: Simulationmentioning
confidence: 99%
“…In 2021, Mahmood et al [19] published an enlarged Cosine generalised family of distributions for dependability modelling: characteristics and applications with simulation analysis, and Muse et al [20] suggested a new flexible form of the loglogistic distribution. Citations [5], [17], and [6] in 2022 explored a family of produced distributions with applications.…”
Section: Introductionmentioning
confidence: 99%